Evaluation of physical and instrumentally determined sensory attributes of Atlantic salmon portions packaged in modified atmosphere and vacuum skin. (July 2021) - Chan, Sherry Stephanie; Skare, Maren; Rotabakk, Bjørn Tore; Sivertsvik, Morten; Lerfall, Jørgen; Løvdal, Trond; Roth, Bjørn
Abstract: Fresh Atlantic salmon ( Salmo salar ) were slaughtered and stored on ice at 0 °C then portioned and packaged six to eight days later in modified atmosphere (CO2 :N2 60:40) packaging (MAP), vacuum skin packaging and open air. All fillet portions were stored in refrigerated conditions at 4 °C. Physical and instrumentally determined sensory quality parameters, including water holding properties, pH, colour, texture and microbiological shelf life, were examined for three weeks. The results showed that both MAP and vacuum skin packaging gave comparable quality in drip loss, water holding capacity, texture and microbiological shelf life. Both packaging groups displayed increased lightness and decreased redness and yellowness throughout storage after filleting. Fillets kept in MAP had consistently lower pH with a darker, more reddish, and yellowish colour than skin packaged fillets. Fillets stored in air had the shortest microbiological shelf life (<13 days) even when they were portioned later. It is concluded that the microbiological shelf life of MAP and skin packaged fillets at 4 °C was around 18–20 days with a limit of 10 6  cfu/g and therefore effectively extends the microbiological shelf life of raw fillets by 1.5 times. Highlights: The quality of salmon fillets packaged in modified atmosphere and vacuum skin were compared. Salmon fillets in both packaging types gave comparable quality. Fillets in MAP had a consistently lower pH. Fillets in MAP had a darker, more reddish and yellowish colour than vacuum skin packaged fillets. MAP and vacuum skin packaged salmon fillets effectively extends microbiological shelf life by 1.5 times.